(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
This article informs about the usage and significance of a wide range of contemporary interactive games effectively and productively through teaching process. Because increasing number of teachers are in need to take advantage of innovative approaches to conduct the lessons in this article, we are about to dive into various ped technological activities which can be used to to conduct the lessons productively